Consolidation of peat and organic soil using electro-osmosis treatment - Yee, Sharon Jia Huey (Curtin University, 2016)
Electro-osmosis is an electrokinetic phenomenon where water is moved through soil under the influence of an electrical field. Commonly applied in soil decontamination, electro-osmosis is also being developed as a ground improvement technique. Successful field trials have been carried out in clay, with limited research in peat and organic soil. This study shows that electro-osmosis expedited consolidation of peat and organic soil, with reduction in moisture content and increase in undrained shear strength.